Artikel Review: Faktor yang Mempengaruhi Persen Biogasoline Minyak Nabati Menggunakan Katalis HZSM-5 dengan Metode Catalytic Cracking - Dewinta Intan Laily; Dina Kartika Maharani (Al-Kimia, 2021)
The increase in fuel consumption of oil has an impact on the energy crisis. Biogasoline is one of the alternative energies that has the potential to solve the problem. The fact that biogasoline results are low is a challenge for further research. One of the methods used to produce biogasoline is the catalytic cracking method. Such methods generally use catalyst to help to speed up the reaction. HZSM-5 is one of the catalysts that has been widely used in various applications. In this review article will compare the value of % biogasoline between several types of crushed vegetable oils with hzsm-5 catalysts using catalytic cracking methods. Based on the results of the analysis it can be known that the method of catalytic cracking using the catalyst HZSM-5 produces a good % biogasoline value so the use of catalyst HZSM-5 is recommended in vegetable oil reactions. In addition, there are factors that affect the value of % biogasoline namely: rector type, operating temperature, reaction time, surface area and pore size catalyst HZSM-5 as well as vegetable oil type.